Mata Hari's Dance in the Context of Femininity and Exoticism - Kolb, Alexandra (Mandrágora, 2025)
The Dutch dancer Mata Hari (alias Mangaretha Gecrtruida Zelle) has achieved un iconic status within 20-century dance history., partly due to her eNecution as a German spy in 1917.